The Effect of Progressive Muscle Relaxation on Stress and Blood Sugar in Diabetes Mellitus Patients - Ika Mustafida; Fitrian Rayasari; Dewi Anggraini; Wati Jumaiyah (Indonesian Journal of Global Health Research, 2024)
Diabetes Mellitus is a chronic condition characterized by impaired insulin production, leading to hyperglycemia. Physically and psychologically, Diabetes Mellitus can cause stress and fluctuations in blood sugar levels. This application aims to determine the effect of Progressive Muscle Relaxation (PMR) on stress and blood sugar levels in Diabetes Mellitus patients through the evidenced based nursing practice. This study used a quasi-experimental method with one group pretest posttest design. Data collection was carried out using the Diabetes Distress Scale (DDS-17) and blood sugar level measurements. Determination of the sample using purposive sampling of 25 Diabetes Mellitus patients. This study showed that there was a decrease in stress scores of 0.162 points and a decrease in blood sugar levels of 8.12 mg/dl after the implementation of Progressive Muscle Relaxation for 3 days. Progressive Muscle Relaxation has been proven to be effective in reducing stress and blood sugar levels in patients with Diabetes Mellitus and can be used as an evidence-based intervention in nursing care for patients with Diabetes Mellitus.